Self‐management of Challenging Behaviours Associated with Autism Spectrum Disorder: A Meta‐Analysis. (7th June 2016) - Carr, Monica E.
Abstract : Objective: A diagnosis of autism spectrum disorder (ASD) is often accompanied by challenging behaviour that may limit the ability to engage in education, employment, or social settings. The purpose of this review was to examine the effectiveness of self‐management interventions in reducing challenging behaviours for individuals diagnosed with ASD. This review included self‐management interventions that specifically targeted a reduction in challenging behaviours as well as studies that specifically targeted skill acquisition and described improvements in challenging behaviours as a collateral effect of the intervention Method: Studies were located by conducting a systematic search of peer‐reviewed literature published in English prior to October 2015. The PsycINFO and ERIC databases were searched. A quality assessment was conducted using the What Works Clearinghouse (WWC) guidelines. A final data set of 12 single‐subject research design studies that met quality standards was subsequently analysed. Treatment effect sizes were calculated using the percentage of non‐overlapping data. Results: Results were analysed by age, gender, symptom severity, presentation of problem behaviour, and the presence of functional behaviour assessments. Results indicated that self‐management interventions are effective at decreasing challenging behaviour for children aged four to 18 years who may be described as either high or low functioning. Conclusions: Self‐management of challenging behaviour was identified as an emerging treatment, and inclusion within a positive behaviour support framework was argued. Important areas for consideration in future research are described.